Buyouts, Private Equity and Performance - Hoyes, A.G. (2010)
This study sought to examine the often overlooked relationships between firm performance and various buyout types for a sample of 276 U.K. buyouts within the period of 1997 – 2006. The buyout types compared include: (1) Private Equity and non-Private Equity backed buyouts (2) Insider vs. outsider-led buyouts (3) Different sources of buyouts. Univariate and Multivariate statistical methods are used to test hypotheses derived from previous empirical evidence and an integration of Agency theory and Strategic Entrepreneurship theory.